2021
DOI: 10.1007/s40857-021-00256-z
|View full text |Cite
|
Sign up to set email alerts
|

A Helmholtz Resonator-Based Acoustic Metamaterial for Power Transformer Noise Control

Abstract: Controlling low-frequency noise propagated by power transformers in urban and industrial areas poses a technical challenge in the design of sound absorbers. Although existing acoustic metamaterials are largely successful as single-band absorbers, they are far from optimal approaches to absorb power transformer noise. As a common method of providing multi-band absorbers, the parallel configuration of multiple individual units leads to the coupling effect, resulting in the absorption coefficient drop. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…[20][21][22][23] Sharafkhani used Helmholtz resonators to control the transformer noise. 24 Guo et al constructed an extended neck Helmholtz resonator and studied its sound absorption capacity. 25 Jena et al demonstrated the use Helmholtz resonators around the duct experimentally, analytically, and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Sharafkhani used Helmholtz resonators to control the transformer noise. 24 Guo et al constructed an extended neck Helmholtz resonator and studied its sound absorption capacity. 25 Jena et al demonstrated the use Helmholtz resonators around the duct experimentally, analytically, and numerically.…”
Section: Introductionmentioning
confidence: 99%
“…Among the present sound-absorbing materials or structures [7][8][9][10][11][12][13], acoustic metamaterials have significant advantages in controlling sound waves in the low-frequency range, and optimizing their structures can enable functionality based on new physical phenomena [14][15][16][17][18][19][20]. For example, Gao et al [14] summarized the basic classification, underlying physical mechanism, application scenarios, and emerging research trends for both passive and active noise-reduction metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, acoustic metamaterials based on Helmholtz resonators and capable of attenuating sound up to 30 dB were developed by Casarini et al [19], which could be applied for noise control in small-scale electroacoustic devices and sensors. Furthermore, Sharafkhani [20] converted a single-band Helmholtz resonator-based sound absorber into a multi-band absorber while maintaining its thickness at 55.1 mm, and perfect absorption was realized for the main components of power transformer noise. Therefore, acoustic metamaterials have been considered as the most promising sound absorbers for noise reduction [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As thin flm metamaterials have advantages in low frequency bands, Yuchao et al [25] developed a membranetype acoustic metamaterial to attenuate the noise of transformers in the frequency range from 100 Hz to 500 Hz. To absorb multiple low frequency components of transformer noise, Sharafkhani [26] connected multiple Helmholtz resonators in series and parallel to obtain the perfect sound absorption at frequencies 100 Hz, 200 Hz, and 300 Hz, respectively. Ye et al [27] proposed a step-by-step structural design method to design plate-type acoustic metamaterial for transformers, which can address single-frequency and multifrequency sound insulation.…”
Section: Introductionmentioning
confidence: 99%